Pelatihan Pemanfaatan Limbah Plastik Untuk Pemuda dan Remaja Masjid - Idel Waldelmi; Afvan Aquino; Aljufri Aljufri (Politeknik Negeri Cilacap, 2022)
The basis for consideration from the service team is to go down to the community in an effort to deal with plastic waste, both plastic waste in households and the surrounding community. The target of the activity is the youth and youth of the mosque with the hope of building creativity and awareness in the youth and youth of the mosque in the neighbourhood of RT/RW 002/012, Sidomulyo Timur Sub-district, Marpoyan Damai District, Pekanbaru. In its implementation, it is carried out by providing counselling on the usefulness value of plastic waste, and training on the value creation of plastic waste as well as assistance/practice in making handicrafts from plastic waste. From the implementation of the service that has been carried out, the results show that there is an increase in knowledge, understanding and the desire of youth and community leaders for the treatment of waste.